Long-life weather-resistant asphalt crack pouring material and preparation method thereof
By adding glue powder, thermoplastic resin, phase change temperature adjustment material and modified calcium carbonate whiskers to the asphalt seam filling material, combined with nanomontmorillonite and a stabilizer of trimethyl coconut oil ammonium chloride, the existing technology has been solved. The problems of asphalt seam filling materials at low temperatures and high temperature debonding have achieved higher adhesion and weather resistance, extending service life and reducing maintenance frequency.
Patent Information
- Application Number
- CN202411349333.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2024-12-27
AI Technical Summary
The existing asphalt seam filling materials are brittle and broken at low temperatures, and have poor adhesion performance, which leads to prone to cracks on the road surface, and poor debonding performance at high temperatures, resulting in frequent maintenance and waste of resources.
Using a combination of 90 to 100 parts of asphalt, 20 to 40 parts of glue powder, 8 to 12 parts of thermoplastic resin, 4 to 10 parts of phase change temperature adjustment material and modified calcium carbonate whiskers, nanomontmorillonite and trimethyl chloride are added. Coconut oil ammonium as a stabilizer, improves the adhesion and weather resistance of the material through rapid shearing and modification treatment.
It significantly improves the adhesion and dispersion stability of the seam filling materials, extends the service life, reduces the road surface maintenance frequency, enhances the high-temperature and low-temperature performance of the materials, and reduces resource waste.
Smart Images

Figure BDA0005061888980000091 
Figure BDA0005061888980000092 
Figure BDA0005061888980000101
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of asphalt caulking materials, and in particular to a long-life weather-resistant asphalt caulking material and a preparation method thereof. Background Art
[0002] Asphalt pavement is a flexible pavement with the characteristics of short traffic closure time, high driving comfort, good wear resistance and anti-skid performance. However, due to the strong temperature sensitivity of asphalt binder, when the ambient temperature is low, asphalt becomes brittle and hard, with low fracture toughness, and is prone to low-temperature brittle fracture, which leads to transverse thermal shrinkage cracks in the pavement; in addition, under the coupling of environmental load and vehicle load, the microcracks generated at the bottom of the asphalt surface layer gradually converge, and eventually reflective cracks from bottom to top will also be generated. When cracks on the road surface are generated, rainwater can enter the interior of the pavement and peel off the aggregate through the weak peeling property of water; and with the application of vehicle load, dynamic water pressure is generated at the bottom of the surface layer, which further scours and accelerates the peeling of aggregates. As a result, cracks are accelerated to expand to form network cracks, cracks, and even large-scale ruptures and collapses, which greatly reduces the road performance and service life of the asphalt pavement. Therefore, it is necessary to carry out preventive maintenance on the asphalt pavement regularly and carry out corresponding treatment at the early stage of crack formation.
[0003] The current grouting technology mainly uses asphalt heated on site and poured into the cracks, or uses emulsified asphalt for grouting. Although both have certain effects on crack treatment, pure asphalt has poor adhesion and cannot be firmly bonded to the fracture surface, and it also faces the problem of brittle fracture again at low temperatures; although emulsified asphalt can be poured into deeper areas, its adhesion to aggregates is also affected by temperature, and it is easy to debond at high temperatures, and its fatigue performance is poor, resulting in maintenance failure, and secondary maintenance is required soon, resulting in a waste of manpower, time and economic resources.
[0004] Chinese patent application 201710831867.5 discloses an asphalt caulking mortar adapted to high temperature environment and its preparation process, which is made of AH-90 asphalt, SBS, cosolvent, stabilizer, softener, resin, and waste rubber powder. The invention adds a large amount of waste rubber powder and rock asphalt, which not only improves the high temperature performance and adhesion performance of the caulking glue, but also enhances its anti-aging performance, and greatly reduces the cost of the product; the addition of resin greatly improves the adhesion between the caulking glue and the crack; the addition of SBS with a certain block ratio and a certain molecular weight has a clear effect on improving the high temperature stability and low temperature ductility of the caulking glue. Compared with the prior art, this material not only improves the high temperature performance and adhesion performance of the caulking glue, but also enhances its anti-aging performance, and greatly reduces the cost of the product, especially improves its high temperature performance, so that it can become a caulking material used in a high temperature environment.
[0005] Chinese patent application 201510507317.9 discloses a road crack filling asphalt material, the invention composition and weight parts are: 40-70 weight parts of road petroleum asphalt, 7-15 weight parts of SBS, 10-20 weight parts of rubber powder, 0.2-0.4 weight parts of miscible stabilizer, 8-40 weight parts of asphalt additives and 0-8 weight parts of filler. The road crack filling asphalt has high elasticity and toughness, stable low temperature resistance, can stretch up to 3 100% cycles under -30℃ environment, and has no flow under high temperature conditions of +80℃, completely achieving the concept of crack filling asphalt that does not crack at low temperature and does not flow at high temperature, can meet the needs of asphalt and cement road crack repair, and is suitable for use in different climatic regions across the country.
[0006] The problem that this solution needs to solve is to develop an asphalt grouting material with excellent weather resistance, strong adhesion to the road surface, good service life and dispersion stability. Summary of the invention
[0007] The purpose of this application is to develop a long-life weather-resistant asphalt caulking material and a preparation method thereof. The asphalt caulking material prepared by this application has both strong adhesion and good dispersion stability, and has extremely high weather resistance and service life. The use of this application can reduce the frequency and cost of road maintenance.
[0008] To achieve the above-mentioned purpose, the present application provides a long-life weather-resistant asphalt caulking material, which comprises 90 to 100 parts of asphalt, 20 to 40 parts of rubber powder, 8 to 12 parts of thermoplastic resin, 4 to 10 parts of phase change temperature regulating material, 6 to 8 parts of modified calcium carbonate whisker, and 4 to 10 parts of stabilizer, wherein the stabilizer comprises a solid stabilizer A and a liquid stabilizer B, and the mass ratio of the solid stabilizer A to the liquid stabilizer B is 1 to 2: 1 to 2;
[0009] The solid stabilizer A is nano-montmorillonite; the liquid stabilizer B is selected from at least one of trimethyl coconut oil ammonium chloride and polyethylene glycol.
[0010] Preferably, the asphalt is petroleum asphalt, and the grade of the petroleum asphalt is at least one of No. 70, No. 80, and No. 90;
[0011] Further preferably, the asphalt is No. 70 petroleum asphalt.
[0012] Preferably, the thermoplastic resin is at least one of ethylene-acrylic acid copolymer, ethylene-methacrylic acid copolymer, and metallocene polyolefin elastomer;
[0013] More preferably, the thermoplastic resin is ethylene-acrylic acid copolymer.
[0014] Preferably, the modified calcium carbonate whiskers are calcium carbonate whiskers modified by a silane coupling agent.
[0015] Preferably, the silane coupling agent is selected from at least one of 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane and 3-aminopropyltriethoxysilane.
[0016] Further preferably, the preparation method of the modified calcium carbonate whisker is: after preparing a solution of ethanol and water in a volume ratio, adding a silane coupling agent and calcium carbonate whisker, stirring at room temperature, washing and filtering with anhydrous ethanol after the reaction is completed, and drying at a constant temperature to obtain the modified calcium carbonate whisker
[0017] In addition, a preparation method for preparing the above-mentioned long-life weather-resistant asphalt caulking material is also disclosed, and the preparation method is: first heat the asphalt to a fluid state, add liquid stabilizer B, and continue to heat up; add rubber powder and phase change temperature control material, and shear quickly; then add modified calcium carbonate whiskers, and continue to shear; then add thermoplastic resin, and continue to shear; finally add solid stabilizer A, stir, and cool to obtain the long-life weather-resistant asphalt caulking material.
[0018] The beneficial effects of this application are:
[0019] The asphalt caulking material described in the present invention is mixed with a large amount of recycled rubber powder, which improves the elastic recovery ability and high-temperature performance of the caulking material. Ethylene-methyl acrylate copolymer is a thermoplastic resin with excellent thermal bonding performance and flexibility. After being mixed, it can greatly improve the adhesion of the caulking material and the fracture surface, and still have high stability in a rainy environment, thereby increasing the ability to resist environmental stress peeling. Modified calcium carbonate whiskers are a micron-level fiber material. After surface modification by a silane coupling agent, the surface activity is enhanced, and the adhesion with asphalt-based materials and thermoplastic resins is enhanced, thereby improving the internal cohesion of the matrix. Through the bridging effect of the fiber, the energy required for the caulking material to crack is further increased, and the generation of microcracks each time it is stressed is reduced, thereby improving the low-temperature stability and fatigue performance of the caulking material; at the same time, the modified calcium carbonate whiskers can also improve the rigidity of the material and enhance its ability to resist deformation at high temperatures. The phase change thermostatic material changes phase after reaching the phase change temperature range, suddenly releasing or absorbing heat from the matrix, thereby achieving automatic temperature control, slowing down the temperature rise of the caulking material at high temperatures, releasing heat to increase the material temperature at low temperatures, enhancing the weather resistance of the caulking material, and exerting good effects at both high and low temperatures. The nano-montmorillonite in the stabilizer is a nano-stabilizer that can form a special interlayer structure of hydrated aluminosilicate components, promoting the uniformity and stability of the blending between the components; trimethyl coconut oil ammonium chloride is a cationic surfactant that can provide emulsification on the one hand, facilitating the caulking material to penetrate into the cracks, and on the other hand, it can also improve the discrete uniformity of the matrix and enhance the stability of storage and transportation; polyethylene glycol has good compatibility with a variety of organic substances and is a good dispersant that can enhance the compatibility of various materials during the preparation and application of potting materials, and further improve the various road performance of the materials. DETAILED DESCRIPTION
[0020] In the description of this application, it should be noted that if the specific conditions are not specified in the examples, the experiments were carried out according to conventional conditions or the conditions recommended by the manufacturer. The reagents or instruments used, if the manufacturer is not specified, are all conventional products that can be purchased commercially.
[0021] Raw material information
[0022] The asphalt is Esso No. 70, Esso No. 80 and Esso No. 90 road petroleum asphalt sold by Shanghai Qun Kang Asphalt Technology Co., Ltd.;
[0023] The rubber powder is produced by Lingshou County Shengfei Mineral Products Processing Plant;
[0024] Ethylene-methacrylic acid copolymer (molecular weight 114) was sold by Shanghai Aojia Industrial Co., Ltd.;
[0025] Ethylene-acrylic acid copolymer (molecular weight 99) was sold by Shanghai Aojia Industrial Co., Ltd.;
[0026] Metallocene polyolefin elastomers were sold by Shanghai Aojia Industrial Co., Ltd.;
[0027] Phase change temperature control material (DTC) is produced by Beijing Qintian Technology Group Co., Ltd.;
[0028] The silane coupling agent was produced by Shenzhen Huanan Xinyang Technology Co., Ltd.;
[0029] 3-Aminopropyltriethoxysilane was produced by Shenzhen South China Xinyang Technology Co., Ltd.;
[0030] 3-Aminopropyltrimethoxysilane was produced by Shenzhen Huanan Xinyang Technology Co., Ltd.;
[0031] Calcium carbonate whiskers were produced by Shandong Jiaying Chemical Technology Co., Ltd.;
[0032] Nano-montmorillonite was produced by Shanghai Wanzhao Fine Chemical Co., Ltd.;
[0033] Trimethyl coconut oil ammonium chloride is produced by Guangzhou Shiming Chemical Co., Ltd.
[0034] Unless otherwise specified, in the following embodiments and comparative examples, the preparation method of a long-life weather-resistant asphalt caulking material is:
[0035] Step 1: After heating the base asphalt to above 170°C until it is fluidized, add trimethyl ammonium coconut oil chloride and continue to heat to 190°C;
[0036] Step 2: Add rubber powder, and rapidly shear at a speed of 2000-3000 rpm for 30-60 minutes, then add DTC phase change temperature control material, and rapidly shear at a speed of 2000-3000 rpm for 10-20 minutes;
[0037] Step 3: adding modified calcium carbonate whiskers, and rapidly shearing at a speed of 2000-3000 rpm for 10 minutes; adding ethylene-methacrylic acid copolymer, and rapidly shearing at a speed of 2000-3000 rpm for 20 minutes;
[0038] Step 4: Add nano-montmorillonite, stir for 15 to 30 minutes, and cool to obtain a long-life weather-resistant asphalt caulking material.
[0039] The preparation method of modified calcium carbonate whiskers is as follows: after preparing 500 ml of solution with ethanol and water in a volume ratio of 1:2, 10 ml of 3-aminopropyltriethoxysilane and 100 g of calcium carbonate whiskers are added, stirring at room temperature for 24 hours, washing and filtering with anhydrous ethanol after the reaction is completed, and drying at a constant temperature of 80°C for 6 hours to obtain modified calcium carbonate whiskers.
[0040] Examples 1-5
[0041] The formula of a long-life weather-resistant asphalt caulking material is shown in Table 1:
[0042] Table 1
[0043] Example 1 Example 2 Example 3 Example 4 Example 5 No. 70 Asphalt 95 copies 90 servings 100 copies 95 copies 95 copies Rubber powder 30 servings 20 servings 40 servings 30 servings 30 servings Thermoplastic resin 10 servings 8 servings 12 servings 10 servings 10 servings Phase change temperature control material 7 servings 4 servings 10 servings 7 servings 7 servings Modified calcium carbonate whiskers 7 servings 6 servings 8 servings 7 servings 7 servings Stabilizer 7 servings 4 servings 10 servings 7 servings 7 servings
[0044] Wherein, the mass ratio of nano-montmorillonite to trimethyl coconut oil ammonium chloride in the stabilizer of Examples 1-3 is 1.5:1.5;
[0045] The mass ratio of nano-montmorillonite to trimethyl coconut oil ammonium chloride in the stabilizer of Example 4 is 1:2;
[0046] The mass ratio of nano-montmorillonite to trimethyl coconut oil ammonium chloride in the stabilizer of Example 5 is 2:1;
[0047] The thermoplastic resin in Examples 1-5 is ethylene-acrylic acid copolymer.
[0048] Example 6
[0049] It is basically the same as Example 1, except that the asphalt is No. 80 asphalt.
[0050] Example 7
[0051] It is basically the same as Example 1, except that the asphalt is No. 90 asphalt.
[0052] Example 8
[0053] It is basically the same as Example 1, except that the thermoplastic resin is ethylene-methacrylic acid copolymer.
[0054] Example 9
[0055] It is basically the same as Example 1, except that the thermoplastic resin is a metallocene polyolefin elastomer.
[0056] Example 10
[0057] The method is basically the same as Example 1, except that the liquid stabilizer in the stabilizer is polyethylene glycol.
[0058] Embodiment 11
[0059] The method is basically the same as Example 1, except that the liquid stabilizer in the stabilizer is composed of trimethyl ammonium coconut oil chloride and polyethylene glycol, and the mass ratio of trimethyl ammonium coconut oil chloride to polyethylene glycol is 1:1.
[0060] Example 12
[0061] The method is basically the same as Example 1, except that the modified calcium carbonate whiskers are modified by 3-aminopropyltrimethoxysilane.
[0062] Example 13
[0063] The method is basically the same as Example 1, except that the modified calcium carbonate whisker is obtained by mixing 3-aminopropyltriethoxysilane and 3-aminopropyltrimethoxysilane in a mass ratio of 1:1 and then modifying the mixture.
[0064] Comparative Examples 1-5
[0065] The formula of a long-life weather-resistant asphalt caulking material is shown in Table 2:
[0066] Table 2
[0067] Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 No. 70 Asphalt 95 copies 95 copies 95 copies 95 copies 95 copies Rubber powder 0 copies 30 servings 30 servings 30 servings 30 servings Thermoplastic resin 10 servings 0 copies 10 servings 10 servings 10 servings Phase change temperature control material 7 servings 7 servings 0 copies 7 servings 7 servings Modified calcium carbonate whiskers 7 servings 7 servings 7 servings 0 copies 7 servings Stabilizer 7 servings 7 servings 7 servings 7 servings 0 copies
[0068] Wherein, the thermoplastic resin in Comparative Example 1 and Comparative Examples 3-5 is ethylene-acrylic acid copolymer;
[0069] The mass ratio of nano-montmorillonite to trimethyl coconut oil ammonium chloride in the stabilizer of Comparative Examples 1-4 is 1.5:1.5.
[0070] Comparative Example 6
[0071] The method is basically the same as Example 1, except that no nano-montmorillonite is added to the stabilizer.
[0072] Comparative Example 7
[0073] The method is substantially the same as Example 1, except that trimethyl coconut oil ammonium chloride is not added to the stabilizer.
[0074] Comparative Example 8
[0075] The method is basically the same as Example 1, except that the mass ratio of nano-montmorillonite to trimethyl coconut oil ammonium chloride in the stabilizer is 1:3.
[0076] Comparative Example 9
[0077] The method is basically the same as Example 1, except that the mass ratio of nano-montmorillonite to trimethyl coconut oil ammonium chloride in the stabilizer is 3:1.
[0078] Comparative Example 10
[0079] The method is substantially the same as Example 1, except that calcium carbonate whiskers are used to replace modified calcium carbonate whiskers.
[0080] Performance Testing
[0081] Test Method
[0082] The softening point and the difference in softening point after 48 hours of separation are tested according to the specification "Test Procedures for Asphalt and Asphalt Mixtures in Highway Engineering" (JTGE20-2011);
[0083] Cone penetration, flow value, elastic recovery and low-temperature tensile test are carried out in accordance with "Pavement Heating Sealant" (JT-T740-2015);
[0084] The softening point pull-out strength after segregation was tested on basalt slabs according to ASTMD4541-2009;
[0085] The rutting factor and fatigue life were obtained by temperature sweep test and linear amplitude sweep test respectively according to the Test Specification for Asphalt and Asphalt Mixture in Highway Engineering (JTG E20-20XX).
[0086] Where: Dry-wet pull-out strength ratio = wet pull-out strength / dry pull-out strength * 100%
[0087] Test Results
[0088] The performance tests of Examples 1-7 are shown in Table 3:
[0089] Table 3
[0090]
[0091] The performance tests of Examples 8-13 are shown in Table 4:
[0092] Table 4
[0093]
[0094]
[0095] The performance tests of Comparative Examples 1-5 are shown in Table 5:
[0096] Table 5
[0097]
[0098]
[0099] The performance tests of Comparative Examples 6-10 are shown in Table 6:
[0100] Table 6
[0101]
[0102]
[0103] Result analysis:
[0104] 1. It can be seen from Example 1 and Comparative Examples 5-7 that, relative to Example 1, no stabilizer was added in Comparative Example 5;
[0105] In Comparative Example 6, only trimethyl coconut oil ammonium chloride was added;
[0106] In Comparative Example 7, only nano-montmorillonite was added, and the performance data are shown in Table 7:
[0107] Table 7
[0108]
[0109] It can be seen from the experimental data that in Comparative Example 5, no stabilizer was added, and the softening point difference of the long-life weather-resistant asphalt caulking material after separation was 7.9°C. Although the addition of nano-montmorillonite or trimethyl coconut oil ammonium chloride alone can also improve the performance of the caulking material, the improvement is very small. On the other hand, it can be seen from Example 1 that when nano-montmorillonite and trimethyl coconut oil ammonium chloride are used together, the improvement in the performance of the caulking material is far beyond expectations, indicating that there is a synergistic effect between nano-montmorillonite and trimethyl coconut oil ammonium chloride.
[0110] And through the experimental data of Example 1, Examples 4-5, and Comparative Examples 8-9 as shown in Table 8, it can be seen that:
[0111] Table 8
[0112]
[0113]
[0114] It can be seen from the data in Table 6 that when the stabilizer nano-montmorillonite and trimethyl coconut oil ammonium chloride are used together, although the performance of the caulking material can still be improved better than when nano-montmorillonite or trimethyl coconut oil ammonium chloride is used alone, due to the excessive content of nano-montmorillonite or trimethyl coconut oil ammonium chloride, cracks will eventually appear in the caulking material during the low-temperature tensile test at -25°C.
[0115] 2. It can be seen from Example 1 and Examples 6-7 that the asphalt in Example 1 is No. 70 asphalt;
[0116] In Example 6, the asphalt is No. 80 asphalt;
[0117] The asphalt in Example 7 is No. 90 asphalt, and the experimental data are shown in Table 9:
[0118] Table 9
[0119]
[0120]
[0121] From the data in Table 7, it can be seen that among the selected No. 70, No. 80 and No. 90 asphalts, all three can pass the low-temperature tensile test, but when combined with other components in the caulking material, No. 70 asphalt is better in improving the performance of the caulking material.
[0122] 3. It can be seen from Example 1, Examples 8-9 and Comparative Example 2 that the thermoplastic resin in Example 1 is an ethylene-acrylic acid copolymer;
[0123] In Example 8, the thermoplastic resin is ethylene-methacrylic acid copolymer;
[0124] In Example 9, the thermoplastic resin is a metallocene polyolefin elastomer;
[0125] No thermoplastic resin was added to the caulking material of Comparative Example 2, and the performance test data are shown in Table 10:
[0126] Table 10
[0127]
[0128] From the performance test results of Example 1 and Comparative Example 2, it can be seen that after adding the thermoplastic resin, the softening point of the caulking material is increased by 11.4°C, and the softening point difference after separation is only 0.4°C; on the other hand, the adhesion and water stability of the caulking material are also improved, among which the dry tensile strength and dry-wet tensile ratio of the thermoplastic resin ethylene-acrylic acid copolymer have the largest improvement rate, with the dry tensile strength improvement rate reaching 51.27%, and the dry-wet tensile ratio increased by 27.27%.
[0129] 4. It can be seen from Example 1 and Comparative Example 3 that, relative to Example 1, the caulking material prepared in Comparative Example 3 does not contain any DTC phase change temperature regulating material. From the data in Table 3, it can be seen that the caulking material prepared in Comparative Example 3 can pass the low-temperature tensile test at -10°C, but has a crack with a length of 2 mm, and cannot pass the low-temperature tensile test at -25°C.
[0130] In contrast, in Example 1, after adding the DTC phase change temperature regulating material, the caulking material can not only pass the low-temperature tensile test, but also the rutting factor at 76°C is increased by 4.3 KPa, and the fatigue life is also increased by 1336 times.
[0131] 5. It can be seen from Example 1, Examples 12-13, Comparative Example 4 and Comparative Example 10 that the calcium carbonate whiskers in Example 1 are calcium carbonate whiskers modified with 3-aminopropyltriethoxysilane;
[0132] The calcium carbonate whiskers in Example 12 are calcium carbonate whiskers modified with 3-aminopropyltrimethoxysilane;
[0133] The calcium carbonate whiskers in Example 13 are calcium carbonate whiskers modified by mixing 3-aminopropyltriethoxysilane and 3-aminopropyltrimethoxysilane in a mass ratio of 1:1;
[0134] In Comparative Example 4, no modified calcium carbonate whiskers were added;
[0135] Unmodified calcium carbonate whiskers were added in Comparative Example 10, and the test data are shown in Table 11:
[0136] Table 11
[0137]
[0138]
[0139] It can be seen from the performance test data in Table 9 that in Comparative Example 10, after adding calcium carbonate whiskers, the caulking material prepared in Comparative Example 2 has improved in all aspects, and the greatest improvement is in low-temperature tensile performance and fatigue life performance, among which the fatigue life number of times is increased by 1700 times.
[0140] When modified calcium carbonate whiskers are added, the surface activity is enhanced after surface modification through silane coupling agent, and the adhesion with asphalt-based materials and thermoplastic resins is enhanced, further improving the dry and wet tensile strength of the caulking material; and through the bridging effect of the fibers, the energy required for the potting material to crack is increased, reducing the generation of microcracks each time it is subjected to force, thereby further improving the fatigue life of the caulking material.
[0141] Comparing Example 1 with Examples 12-13, the performance of the caulking material is further improved when the modified calcium carbonate whiskers obtained by compounding 3-aminopropyltriethoxysilane and 3-aminopropyltrimethoxysilane are added.
[0142] 6. It can be seen from Example 1 and Comparative Example 1 and Table 12 that:
[0143] Table 12
[0144]
[0145]
[0146] It can be seen from the experimental data that compared with Example 1, no rubber powder was added in Comparative Example 1. Although the tensile test was passed, the pull-out strength and fatigue life were greatly reduced. Compared with Example 1, the dry-wet pull-out strength ratio was reduced by 13.05%, and the fatigue life was reduced by 1659 times.
[0147] 7. It can be seen from Examples 1 and 10-11 that, relative to Example 1, the liquid stabilizer in Example 10 is polyethylene glycol;
[0148] The liquid stabilizer in Example 11 is composed of trimethyl coconut oil ammonium chloride and polyethylene glycol. As can be seen from Table 4, trimethyl coconut oil ammonium chloride and polyethylene glycol are used as liquid stabilizers respectively, and their effects on improving the performance of the caulking material are similar. However, when trimethyl coconut oil ammonium chloride and polyethylene glycol are used in combination, the performance of the caulking material is further improved due to the synergistic effect of the two.
[0149] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications made without departing from the spirit and principles of the present invention shall be equivalent replacement methods and shall be included in the protection scope of the present invention.
Claims
1. A long-life weather-resistant asphalt caulking material, characterized in that: By mass: 90-100 parts of asphalt, 20-40 parts of rubber powder, 8-12 parts of thermoplastic resin, 4-10 parts of phase change temperature control material, 6-8 parts of modified calcium carbonate whisker, 4-10 parts of stabilizer, wherein the stabilizer comprises solid stabilizer A and liquid stabilizer B, and the mass ratio of solid stabilizer A to liquid stabilizer B is 1-2:1-2; The solid stabilizer A is nano-montmorillonite; The liquid stabilizer B is selected from at least one of trimethyl coconut oil ammonium chloride and polyethylene glycol.
2. The long-life weather-resistant asphalt caulking material according to claim 1 is characterized in that: The asphalt is petroleum asphalt, and the grade of the petroleum asphalt is at least one of No. 70, No. 80, and No.
90.
3. The long-life weather-resistant asphalt caulking material according to claim 1, characterized in that: The thermoplastic resin is at least one of ethylene-acrylic acid copolymer, ethylene-methacrylic acid copolymer and metallocene polyolefin elastomer.
4. The long-life weather-resistant asphalt caulking material according to claim 1, characterized in that: The modified calcium carbonate whisker is a calcium carbonate whisker modified by a silane coupling agent.
5. The long-life weather-resistant asphalt caulking material according to claim 4 is characterized in that: The silane coupling agent is selected from at least one of 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane and 3-aminopropyltriethoxysilane.
6. The long-life weather-resistant asphalt caulking material according to claim 4, characterized in that: The preparation method of the modified calcium carbonate whisker comprises: preparing a solution with ethanol and water in a volume ratio, adding a silane coupling agent and calcium carbonate whisker, stirring at room temperature, washing and filtering with anhydrous ethanol after the reaction is completed, and drying at a constant temperature to obtain the modified calcium carbonate whisker.
7. A method for preparing the long-life weather-resistant asphalt caulking material as claimed in any one of claims 1 to 6, characterized in that: The preparation method comprises the following steps: firstly heating the asphalt to a fluid state, adding a liquid stabilizer B, and continuing to heat up; then adding rubber powder and a phase change temperature regulating material, and rapidly shearing; then adding modified calcium carbonate whiskers, and continuing to shear; then adding a thermoplastic resin, and continuing to shear; and finally adding a solid stabilizer A, stirring, and cooling to obtain a long-life weather-resistant asphalt caulking material.
